ChemInform Abstract: mCPBA‐Mediated Metal‐Free Intramolecular Aminohydroxylation and Dioxygenation of Unfunctionalized Olefins. Issue 48 (December 2015) - Liu, Gong‐Qing; Li, Lin; Duan, Lili; Li, Yue‐Ming
Abstract: Aminohydroxylation product (IVb) can be carried out at gram‐scale and the hydroxyl group can be further converted to a variety of different functional groups via conventional group transformation reactions such as azidation, bromination, acetylation, carboxylation and Swern oxidation.